Effectiveness of a gratitude app at reducing repetitive negative thinking as a transdiagnostic risk factor in the general population: Results from a pragmatic randomized controlled trial - Kalon, Lina S.; Freund, Henning; Rinn, Alina; Watkins, Philip C.; Zarski, Anna-Carlotta; Lehr, Dirk (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Background Repetitive negative thinking (RNT) has been identified as a transdiagnostic factor relevant to the prevention and treatment of a variety of mental disorders, including depression. Low-threshold interventions to reduce RNT are needed that have the potential to reach the general population. Gratitude exercises have been assumed to be widely accepted, easy and enjoyable to conduct and might, therefore, be a promising approach. This study investigated the effectiveness of a low-threshold, mobile gratitude intervention at reducing RNT in the general population. Methods In a pragmatic randomized controlled trial(N = 352), the gratitude app was compared to a waiting-list control condition, both with unrestricted access to care-as-usual. The primary outcome was RNT four weeks after randomization with extended follow-up at three months. Symptoms of depression were assessed as a secondary outcome. Results ANCOVA using an intention-to-treat sample indicated significantly lower levels of RNT in the gratitude intervention group(d = 0.39), with more pronounced effects in a subsample(35 %) screened positive for depression(d = 0.55) relative to the majority scoring below the threshold for depression(d = 0.35). A similar pattern was observed for depression, with an average effect of d = 0.41. Moderation analyses employing the Johnson-Neyman technique found that individuals reporting average or above-average levels of RNT or depression benefitted significantly. Limitations Given the presence of gratitude in public media and a readily-available alternative gratitude exercise for controls, treatment-diffusion bias could have led to an underestimation of effects. Conclusion A comparably-easy and focused mobile gratitude intervention, using written notes and photos to collect and share moments of gratitude, reduces RNT and symptoms of depression in the general population. Gratitude interventions may broaden the repertoire of transdiagnostic interventions for prevention and treatment.
Keywords: Repetitive negative Thinking; Depression; Transdiagnostic; Gratitude; Mobile Intervention; Positive Psychology